1989
DOI: 10.1111/j.1524-4725.1989.tb03236.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Glove Perforation in Dermatologic Surgery

Abstract: Twenty-eight of 240 (11.7%) pairs of sterile surgical gloves collected from dermatologic surgery clinics had perforations. Only 17.1% of these perforations were known to the wearer at the time of surgery. Equal numbers of perforations were found in gloves of operators and assistants. Perforations were more numerous in dominant-handed gloves. Dermatologic surgeons should consider the incidence of unknown glove perforation when planning surgeries in patients with infectious diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 14 publications
3
12
1
Order By: Relevance
“…Perforation rates in ophthalmologic procedures varied from 0.3% to 16%, whereas perforation rates in cardiac and general surgery ranged from 24% to 31.5% 7,8 . A previous glove study of dermatologic simple excisions and Mohs micrographic surgical procedures demonstrated perforation rates of 11.7% for sterile gloves 9 . Our study further confirms that routine dermatologic procedures can be performed safely using nonsterile examination gloves without endangering the patient or the health care provider.…”
Section: Discussionsupporting
confidence: 77%
“…Perforation rates in ophthalmologic procedures varied from 0.3% to 16%, whereas perforation rates in cardiac and general surgery ranged from 24% to 31.5% 7,8 . A previous glove study of dermatologic simple excisions and Mohs micrographic surgical procedures demonstrated perforation rates of 11.7% for sterile gloves 9 . Our study further confirms that routine dermatologic procedures can be performed safely using nonsterile examination gloves without endangering the patient or the health care provider.…”
Section: Discussionsupporting
confidence: 77%
“…[7][8][9][10][11][12][13][14] As a result, wearing double sets of gloves has been advocated during dermatologic surgery. [7][8][9][10][11][12][13][14] As a result, wearing double sets of gloves has been advocated during dermatologic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…47 Two studies in the dermatologic surgery setting also showed that there is a 5.5% to 11.5% likelihood of single-or outerglove perforation during dermatologic operations, the majority of which are unrecognized by the dermatologist. 45,48,49 With double gloving, the risk of inner-glove perforation is reduced to 3.8%, and innerand outer-glove perforations seldom matched. 45 Thus, the evidence is strong that double gloving significantly reduces the risk of percutaneous exposures to blood, and the slight adjustment necessary to maintain dexterity is well worth the benefits.…”
Section: Universal Precautionsmentioning
confidence: 97%